Cuneiform orthography of the stops in Alalaḫ VII Akkadian - Popova, Olga V. (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2016)
This article presents a statistical analysis of signs of the CV type and their values as used for stop consonants in Alalaḫ VII documents. Comparing the Alalaḫ VII syllabary with those of OAkk, OAss and Mari, I show that it had not been systematized by the time of the city’s destruction, and that one cannot speak of an adequate written representation for all voiced, voiceless and emphatic stops in Alalaḫ VII. Nevertheless, the syllabary does show a tendency towards a rational distribution of the signs used. This research also demonstrates that it may be misleading to consider Alalaḫ VII the direct source of borrowing of Hittite cuneiform.